2000
DOI: 10.1007/s003830000393
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal atresia and tracheoesophageal fistula: a review of 25 years' experience

Abstract: During a 25-year period (1972-1996), 585 patients with esophageal atresia with or without tracheoesophageal fistula were treated at the Department of Pediatric Surgery, SMS Medical College, Jaipur, India. Increasing awareness of the anomaly has led to early detection and referral with fewer pulmonary complications. For purposes of analysis the period has been divided into five phases, with a steady decline in overall mortality observed from 95.4% in phase 1 to 41% in phase V. Although postoperative complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 0 publications
3
20
0
4
Order By: Relevance
“…40.7% cases reached within first 24 hours in spite of 75% deliveries at hospital. 6 Agarwal et al in AIIMS hospital reported that the patients presenting within 24 hours were 44% and similar data (46%) was also obtained by Sharma AK et al 7,8 Traveling long distance, poor transport system and poverty are also the contributory factors.…”
Section: Discussionsupporting
confidence: 61%
“…40.7% cases reached within first 24 hours in spite of 75% deliveries at hospital. 6 Agarwal et al in AIIMS hospital reported that the patients presenting within 24 hours were 44% and similar data (46%) was also obtained by Sharma AK et al 7,8 Traveling long distance, poor transport system and poverty are also the contributory factors.…”
Section: Discussionsupporting
confidence: 61%
“…Sharma et al gave a method of suturing the upper puch to the anti spatulated end of the lower pouch in 1994. This was followed by circular myotomy which created a large anastomosis [8]. Melek et al gave a plus shaped incision over the upper pouch creating a zigzag anastomosis [2,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The nature of anastomosis has been controversial and different approaches have been suggested in literature [2,8,9,14]. The earliest teaching still used in the majority of centers worldwide has been a circular anastomosis in a single transverse plane [10,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] A transverse circular anastomosis by extra pleural approach with proper mobilization of both the upper and lower esophageal pouches is the surgical procedure of choice. 4,5 Even following a proper anastomosis, the condition is often complicated by anastomotic leaks and strictures. 6 These complications mandate either re-exploration or a gastrostomy as a life-saving maneuvers.…”
Section: Introductionmentioning
confidence: 99%